Targeting FBXO22 enhances radiosensitivity in non-small cell lung cancer by inhibiting the FOXM1/Rad51 axis - Yunshang Chen; Yun Zhou; Xue Feng; Zilong Wu; Yongqiang Yang; Xinrui Rao; Rui Zhou; Rui Meng; Xiaorong Dong; Shuangbing Xu; Sheng Zhang; Gang Wu; et al. (Cell Death and Disease, 2024)
Abstract Radioresistance is a major constraint on the efficacy of lung cancer radiotherapy, but its mechanism has not been fully elucidated. Here, we found that FBXO22 was aberrantly highly expressed in lung cancer and that FBXO22 knockdown increased the radiosensitivity of lung cancer cells. Mechanistically, FBXO22 promoted Rad51 gene transcription by increasing the level of FOXM1 at the Rad51 promoter, thereby inducing the formation of lung cancer radioresistance. Furthermore, we found that deguelin, a potential inhibitor of FBXO22, enhanced radiosensitivity in an FBXO22/Rad51-dependent manner and was safely tolerated in vivo. Collectively, our results illustrate that FBXO22 induces lung cancer radioresistance by activating the FOXM1/Rad51 axis and provide preclinical evidence for the clinical translation of this critical target.